2016
DOI: 10.1002/sdtp.10722
|View full text |Cite
|
Sign up to set email alerts
|

41-2:Invited Paper: Quantum Dots and Aligned Quantum Rods for Polarized LC Backlights

Abstract: A backlight that emits linearly polarized light would make it possible to increase the transmission through the first polarizer by a factor two. We used quantum rods that have a CdSe core that emits partially polarized yellowish green light (around 570 nm) and a CdS bulk that absorbs blue. The quantum rods can be aligned with their long axis parallel to an applied electric field with sufficient amplitude. The resulting layer emits linearly polarized light with a high degree of polarization. Such a layer can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Ghent University showed that QRs can be aligned with their long axis parallel to an applied electric field with sufficient amplitude by using the dip-coating technique. 18 A substrate with ITO electrodes in a finger pattern was slowly pulled out of a suspension with CdSe/CdS quantum rods while an ac electric field was applied. The Ghent researchers demonstrated that this procedure makes it possible to align and fix the QRs in the desired orientation.…”
Section: And (B) An Eco-qd Array On a Twisted-nematic Lc Cell Architementioning
confidence: 99%
See 1 more Smart Citation
“…Ghent University showed that QRs can be aligned with their long axis parallel to an applied electric field with sufficient amplitude by using the dip-coating technique. 18 A substrate with ITO electrodes in a finger pattern was slowly pulled out of a suspension with CdSe/CdS quantum rods while an ac electric field was applied. The Ghent researchers demonstrated that this procedure makes it possible to align and fix the QRs in the desired orientation.…”
Section: And (B) An Eco-qd Array On a Twisted-nematic Lc Cell Architementioning
confidence: 99%
“…Images from Ghent University include (a) top left: the fluorescence of oriented QRs under a polarizing microscope; top right: the dependency of the PL intensity on the azimuth angle of the polarizer; and bottom: the fluorescence microscopy of a particular region on the substrate with oriented QRs with the polarizer parallel (left) and perpendicular (right) to the applied electric field 18 . (b) Hong Kong University of Science and Technology's image shows the process flow of QR‐dispersed aligned LCP films 19 …”
Section: Quantum‐dot Leds (Qleds)mentioning
confidence: 99%
“…However, the vigorous task of using these QRs for the desired purpose is to align them in a perfectly unidirectional array so as to get higher polarized light emission. Several approaches have been projected such as electric field-assisted assembly [5], using photo-alignment layer [6], arrangement in liquid crystal defects [7], solvent-based assembly [8] and embedding the QRs in nanofiber sheets using electrospinning [9].…”
Section: Introductionmentioning
confidence: 99%
“…LCDs operate with polarized light and therefore a linear polarizer is placed between the backlight and the LC panel, which absorbs typically 50% of the light. A backlight with intrinsic polarization is thus preferred to improve the overall optical efficiency [3].…”
mentioning
confidence: 99%